The Impact of Breakwater Type on Hydrodynamic Environment in Semi-Closed Harbor - WU Qiong; LI Mugui; LUO Huan (Renmin Zhujiang)
Affected by breakwater construction,the water exchange of semi-closed harbor is often not smooth,and the self-purification ability is weak.To study the influence of different types of breakwater on the hydrodynamic environment in semi-closed harbor,the article took a typical semi-enclosed port in the Pearl River estuary,Xiangzhou fishing port as an example to analyze the differences of water exchange ability and the transport law of pollutants under the layout scheme of breakwater with opening width including 20、40、60、100 m.The results showed that,compared with the fully closed breakwater scheme,under the scheme of opening width of 20、40、60、100 m,the half exchange period of water in the harbor increased by 5.0 hours,11.0 hours,14.0 hours and 14.5 hours.The scheme with opening more than 40m was better than 20 m.However,there was no significant difference in the effect of the three schemes of opening 40、60、100 m.Considering the influence of regional pollution source input,under the scheme of breakwater opening,the concentration of inorganic nitrogen increased by 0.2~0.4 mg/L in the area near the opening.It further aggravated the pressure of inorganic nitrogen pollution in the northern part of the harbor,while the quality of water environment in the southern part of the harbor was improved due to the enhancement of water exchange ability.